Waviness and straightness of cylinder and textured piston ring tribo pair. Issue 2 (13th April 2015) - Zavos, Anastasios; Nikolakopoulos, Pantelis George
Abstract : Purpose: – The purpose of this paper is to review and to provide a dipper understanding of what happens to piston rings and cylinder surfaces when manufacturing errors depicted, such as waviness and straightness. The mechanism of friction and the piston ring structural integrity, due to the surface irregularities, are analyzed either for smooth ring surface or for artificial textured, while piston ring floats into the piston groove or not. Design/methodology/approach: – In this work two tribological models of a piston ring- cylinder package are presented using CFD analysis. Initially, the piston ring is considered as a secured ring in the groove of piston (secured ring) while in second model, the piston ring floats into the piston groove (free ring). Findings: – Increasing the number of waves across the piston ring thickness, the structural integrity of the ring is strongly influenced. Piston ring with surface texturing reduces the mean friction force, under the consideration of cylinder straightness. The gas leaks due to existence of the ring gap, affects significantly the maximum mechanical stresses. Originality/value: – The novelty of this paper is the analysis of manufacturing errors, such as waviness and straightness either for smooth or for artificial textured piston ring. In particular, the piston ring structural integrity investigated while chamber gas pressure leaks through the ring gap or not. The number of the waves, their amplitude and the fluid velocity are also taken into consideration.